Comparative evaluation of push-out bond strength of AH-Plus, MTA-Fillapex and Epiphany SE root canal sealers: An Ex-Vivo study - Sagolsem Chandarani; Mohan Gundappa; Zoya Chowdhary; Deepika Singh; Neeti Swarup; Shalabh Mehrotra (Wolters Kluwer Medknow Publications, 2022)
Background: A successful root canal (RC) treatment depends upon creation of a fluid impervious seal that is commonly built by using a RC sealer along with gutta-percha. The bond strength of the RC sealer is a hallmark as it will minimize the risk of treatment failure by reducing the possibility of filling detachment from dentin. Aim: To evaluate and compare the push-out bond strength of AH-Plus and MTA-Fillapex with Gutta-Percha and Epiphany Self Etch/Resilon system using the Universal Testing Machine. Materials and Method: About 60 mandibular premolars with single canals were prepared apically with Hyflex CM files upto size #30. Out of total, 20 teeth were obturated with AH-Plus/GP (group 1), 20 with MTA-Fillapex/GP (group 2), and other 20 with Epiphany Self Etch/Resilon system (group 3). Teeth were sectioned into three slices of 2 mm each and were subjected to Universal Testing Machine. Statistical Analysis: The data obtained were tabulated and statistically evaluated using SPSS version 21.0 statistical analysis software (IBM, Chicago, Illinois, USA). Results: The mean push-out bond strength was highest for AH-Plus (14.32 MPa) followed by MTA-Fillapex (12.18 MPa) and then Epiphany SE (8.44 MPa). The results were statistically significant. Conclusion: Significantly, higher push out bond strength was displayed by AH-Plus sealer than MTA-Fillapex and least being Epiphany SE sealer. The push out bond strength was significantly highest at apical third and lowest at coronal third.